Paracanthocobitis putaoensis, a new loach species (Cypriniformes: Nemacheilidae) from the Irrawaddy basin in northern Myanmar - Lin, Feng; Chen, Zhi-Ying; Myint, Khin Mar; Chen, Xiao-Yong (Zootaxa, 2023)
Paracanthocobitis putaoensis sp. nov. is described based on analysis of morphological and molecular data (cytochrome c oxidase subunit I—COI). The new species was collected from the Mali Hka River, a tributary of the Irrawaddy River near Putao in Kachin State in northern Myanmar. It can be easily distinguished from all other species of the genus Paracanthocobitis by an incomplete lateral line, a suborbital groove in adult males, and a well-developed axillary pelvic lobe. Phylogenetic relationships of the genus Paracanthocobitis based on the mitochondrial COI locus are revealed for the first time. Maximum likelihood and Bayesian inference phylogenetic analyses indicate that the new species forms an independent clade. Both morphological and molecular phylogenetic analyses suggest that P. putaoensis is a new species.